Comparing The Effects of Lipiflow and IPL Before and After Treatments in Patients with Meibomian Gland Dysfunction - Ojha, Meenakshi; Ranjan, Jai Prabhat (Journal of Neonatal Surgery, 2025)
Background: Meibomian Gland Dysfunction (MGD) is a leading cause of evaporative dry eye and ocular surface disease. It results from obstruction or altered secretion of the meibomian glands, causing tear film instability, inflammation, and discomfort. Effective treatment is essential to prevent long-term ocular surface damage. Among the available therapies, Intense Pulsed Light (IPL) and LipiFlow thermal pulsation have shown promising outcomes. This study aimed to compare the clinical efficacy of IPL and LipiFlow in improving tear film stability, lipid layer quality, and meibomian gland structure in patients with MGD over a six-month period. Materials and Methods: A prospective clinical trial was conducted on 50 patients diagnosed with MGD. All participants underwent baseline assessments including the Ocular Surface Disease Index (OSDI), Tear Break-Up Time (TBUT), Schirmer’s Test I (with topical anesthesia), and LipiView imaging. Patients were randomly assigned into two equal groups: Group 1 (n = 25): Received IPL therapy Group 2 (n = 25): Received LipiFlow therapy Results: Both treatment groups showed a significant improvement in TBUT, indicating enhanced tear film stability. A notable reduction in lipid layer thickness (LLT) and meibomian gland dropout was also observed in both groups. However, Schirmer’s test values remained largely unchanged in both groups. While both modalities provided comparable clinical outcomes, IPL was found to be more cost-effective, whereas LipiFlow offered greater efficiency in treatment duration and efficacy Conclusion: IPL and LipiFlow therapies are both effective in the long-term management of MGD, significantly improving tear film parameters and glandular health. While clinical improvements were similar, IPL may be preferred for its cost-efficiency, and LipiFlow for its enhanced treatment performance. Further studies with larger cohorts are needed to validate these findings and support individualized treatment planning